👤
Negruteo
a fost răspuns

E x = (x-3)² + 2(3+x)(x-3) - (x-2)² - ( x-1)(1+x)​

Răspuns :

Matei

Răspuns:

[tex]\displaystyle{ E(x) = x^{2} -10x - 12 }[/tex]

Explicație pas cu pas:

[tex]\displaystyle{ E(x) = (x-3)^{2} + 2(3+x)(x-3) - (x-2)^{2}-(x-1)(1+x) }[/tex]

[tex]\displaystyle{ E(x) = x^{2} - 6x + 9+2\cdot(x^{2} - 9) - (x^{2}-4x+4)-(x^{2}-1) }[/tex]

[tex]\displaystyle{ E(x) = x^{2} - 6x + 9+2x^{2}-18-x^{2}+4x-4-x^{2}+1 }[/tex]

[tex]\displaystyle{ E(x) = x^{2} + 2x^{2} - x^{2} - x^{2} -6x +4x + 9 - 18 - 4 + 1 }[/tex]

[tex]\displaystyle{ E(x) = x^{2} \cdot (1+2-1-1) - x \cdot (6 + 4) -9 -4 + 1 }[/tex]

[tex]\displaystyle{ E(x) = x^{2} \cdot 1 - 10x -13 + 1 }[/tex]

[tex]\displaystyle{ E(x) = x^{2} -10x - 12 }[/tex]